1990
DOI: 10.1093/infdis/162.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Potential of Giardiasis in Domestic Ruminants

Abstract: This study was conducted to assess the prevalence and zoonotic potential of giardiasis in domestic ruminants. Prevalence of infection was 17.7% in sheep and 10.4% in cattle and was significantly higher in lambs and calves (35.6% and 27.7%, respectively). Naturally infected lambs released cysts intermittently for months. Giardia trophozoites from sheep had typical claw hammer-shaped median bodies and were successfully cultured in TYI-S-33 medium, and cytosolic, cytoskeletal, and membrane fractions exhibited pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
2
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 18 publications
2
56
2
1
Order By: Relevance
“…M a n u s c r i p t 15 Younger dogs were significantly more likely to be Giardia positive by IFAT but this risk factor was not found to be significant using PCR. Previous studies have implicated that tests with a lower sensitivity may result in biased estimation of prevalence and associated risk factors in older animals where the intensity of cyst excretion is lower (Buret et al, 1990;Olson et al, 1997). Dogs that were allowed to scavenge and those that were not fed commercial diets were at significantly higher risk of being Giardia positive by IFAT and PCR respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M a n u s c r i p t 15 Younger dogs were significantly more likely to be Giardia positive by IFAT but this risk factor was not found to be significant using PCR. Previous studies have implicated that tests with a lower sensitivity may result in biased estimation of prevalence and associated risk factors in older animals where the intensity of cyst excretion is lower (Buret et al, 1990;Olson et al, 1997). Dogs that were allowed to scavenge and those that were not fed commercial diets were at significantly higher risk of being Giardia positive by IFAT and PCR respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, diagnostic tests with a low sensitivity may also result in a biased estimation of prevalence and associated risk factors in older animals such as cattle for example, where cyst excretion is lower (Buret et al, 1990;Olson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Mémoire Parasite, 2007, 14, 309-312 sible that with only one sample that the prevalence may have been somewhat underestimated (Buret et al, 1990;Ralston et al, 2003). Longitudinal studies have demonstrated that following animals over time will affect prevalence rates considerably.…”
Section: Discussionmentioning
confidence: 99%
“…are two of the most common protozoan parasites distributed world wide, infecting a wide variety of mammalian hosts (Wolfe 1992;Zajac 1992;Scott et al 1994;Olson et al 1995). Hosts are infected with Giardia through the ingestion of cysts either by the fecal -oral route or the consumption of contaminated water (Meyer 1985;Buret et al 1990;Xiao 1994). Once ingested, the cysts excyst in the duodenum, releasing trophozoites that divide by longitudinal binary fisson, colonizing the small intestine of the host (Kirkpatrick and Farrell 1982;Wolfe 1992;Olson et al 1995).…”
mentioning
confidence: 99%